P264 Global treatment guidelines and patterns in COPD: focus on triple therapy. (12th November 2019) - Sharma, N; Singh, B; Siddiqui, MK; de Nigris, E; Holmgren, U; Cabrera, C; Arnetorp, S
Abstract : Introduction and objectives: To review treatment guidelines for COPD and disease patterns across countries, and compare these with recommendations in the 2018 GOLD Report, with a focus on triple therapy. Methods: A targeted Embase ® /MEDLINE ® literature search was performed to identify COPD treatment guidelines (the most recent update) and studies of real-world treatment patterns in patients with moderate-to-very severe COPD (January 2006–March 2017) in Australia, Canada, China, France, Germany, Italy, Spain, the UK and the USA, all of which have at least one set of national guidelines for COPD management. Results: Fifteen COPD guidelines (13 national/2 global) and 45 studies on treatment patterns were reviewed. Overall, national guidelines broadly reflected the 2018 GOLD Report, with recommendations for COPD treatment based on the severity of airflow limitation, symptoms and exacerbations. No guidelines provided recommendations regarding inhaler device nor expressed a preference for a particular device type. All guidelines recommended escalation to triple therapy for symptomatic patients on dual therapy with frequent exacerbations, but differed as to whether triple therapy should be a step-up from LAMA/LABA or ICS/LABA. Guidelines differed in terms of COPD assessment and classification. Notably, no guidelines other than the GOLD Report used A–D categories based on symptoms/exacerbation risk. In general, the real-world pattern of care diverged from GOLD recommendations. In several countries, if compared strictly with guidelines, ICS-containing regimens were often over-prescribed, i.e. prescribed to low-risk patients. The use of dual and triple therapy was noted in patients with severe airflow limitation. However, use of triple therapy was reported in 60% of patients with only mild-to-moderate COPD severity, despite being prescribed less frequently than recommended in GOLD D patients overall. Conclusions: Although national guidelines for COPD treatment generally reflected the 2018 GOLD Report, real-world treatment patterns deviated from GOLD recommendations. No guidelines other than the GOLD Report used A–D categories based on symptoms/exacerbation risk. Future national guidelines should also consider recent updates to treatment recommendations in the 2019 GOLD Report and provide more precise guidance on drugs to be used based on exacerbation risk, symptoms and eosinophil levels.